(untitled) (Research, Society and Development, 2020)
Stroke is a disabling disease, with high mortality, requiring rapid identification of signs and symptoms for immediate intervention. This study aimed to report the experience about the application of the Nursing Process (NP) in a Stroke Unit. It is an experience report, with a qualitative approach, about the nurses’ experience of a Stroke Unit in view of the application of NP. The NP presented a diagnostic instrument and a nursing intervention instrument based on the main changes that the patient diagnosed with a stroke can present. However, it continued without updates since 2009. All the instruments constructed containing the diagnoses, results and nursing interventions related to the stroke patient were gathered and kept in a single document folder at the U-Stroke for consultation by nurses during the shift. The NP was reformulated, including expected results, new activities and design, providing better acceptance and applicability by the nursing team. The adoption of new instruments for the operationalization of the NP generated a demand for activities, improving the assistance and care provided to the patient.